PC Kiosk Trends in Rural India - Toyama, Kentaro; Kiri, Karishma; Menon, Deepak; Sethi, Suneet; Pal, J.; Srinivasan, Janaki (E-Learning and Digital Media, 2006)
This article presents a series of preliminary, quantitative results on rural PC kiosks in India. An analysis of the data confirms many expected trends and correlations and shows that kiosks still face the challenge of sustainability as a business. This study is based on questionnaires presented to kiosk operators and customers of kiosks operated or franchised by Drishtee and n-Logue, two for-profit rural kiosk companies that operate in various geographies throughout India. Recurring surveys are being run with three questionnaires concerning the daily operation and demographic context of the kiosks. The recurring questionnaires will be repeated once a quarter for three years; the results for this article are from the first two sets only.